A solid acid catalysed one-pot selective approach for 2, 5-diformylfuran synthesis from fructose/carbohydrate feedstocks. Issue 16 (29th July 2022) - Chauhan, Arvind Singh; Kumar, Ajay; Bains, Rohit; Das, Pralay
Abstract : A user-friendly and recyclable solid acid (Amberlite IR 120 H + form resin) was explored for 2, 5-diformylfuran (DFF) synthesis directly from low-cost feedstocks such as fructose, table sugar, sugarcane molasses and jaggery. Abstract : A metal catalyst free synthesis of 2, 5-diformylfuran (DFF) from fructose has been established using a one-pot greener approach. A user-friendly solid acid (Amberlite IR 120 H) was explored for the transformation of fructose into DFF to achieve the highest yield. High chemo-selectivity, recyclability of the solid acid up to seven cycles, and scalable and environmentally benign approaches are some remarkable advantages of the present process. In addition, the devised process was used to obtain DFF from a variety of low-cost feedstocks including fructose, sugar, sugarcane molasses, and jaggery, in an acceptable yield.